Upaya Yuridis Dan Sosiologis Kantor Urusan Agama Dalam Pencegahan Pernikahan Usia Dini - Ahmad Wafiq; F. Setiawan Santoso (Universitas Cokroaminoto Yogyakarta, 2017)
Because of the strict regulation, the Office of Religious Affairs (KUA) needs to minimize the implementation of early marriage. KUA Jetis sub-district, Bantul Regency has conducted juridical and sociological efforts based on qualitative research organized. Through documentation, observation and interviews with KUA employees and sub-district employees, these conclusions were obtained.